Al-Sakaki’s Rrhetoric in the View of Scholars between Denial and Support - Bettahar, Benissa (Dirasat: Human and Social Sciences, 2025)
Objectives: Some of modern scholars saw that Al-Sakaki’s rhetoric represents a stage of decline in the science of rhetoric; it contributed negatively to introducing philosophy into this science, while another trend stated that he had undeniable contributions to the development of the sciences of rhetoric in his era. This research aims to present a set of opinions put forward by each trend. Methods: This research was based on an analytical deductive approach, and the research plan included an introduction to the objectives of the book "Miftah Al-Ulum" and its characteristics, and three topics, the first of which dealt with criticism of Al-Sakaki’s rhetorical study, the second studied the appreciation of Al-Sakaki’s efforts in Arabic rhetoric, and the third was devoted to studying Al-Sakaki’s rhetoric in light of modern stylistics. Results: accusing Al-Sakaki of being the reason for the stagnation of Arabic rhetoric is a judgment far from fairness; he tried to develop an integrated theory in "literary science", to be a natural result of the theory of "systems" of Al-Jurjani. Conclusions: Al-Sakaki addressed some issues related to stylistic displacement, including what came in the chapter on news; and described this departure as being one of the basics of rhetoric in literary discourse, and such procedures converge with some modern stylistic concepts.